Pénibilité au travail : reclasser ou prévenir ? - Franck Héas (Perspectives Interdisciplinaires sur le Travail et la Santé)
Workers’ health may be directly and irreparably compromised by the difficulty of some jobs and/or functions. The legal framework for work difficulty takes several paths. A gradual or early withdrawal from the labour market may be considered first. The awarding of financial compensation to the employee who worked or continues to be employed in a difficult environment is also possible. The existing legal obligation of reclassification in the case of incapacity is also another possibility that can adjust the contractual work relationship and thus offset the effects of work difficulty. However, beyond these different options, improvement of working conditions based on a prevention logic is the only alternative for taking the difficulty into account, and therefore limiting the impact of certain work environments on human health.